Influence of Augmented Reality for the learning of Geometric Solids in Primary School students - Buitrón-Luna, Juan (2021)
Currently, technological advances have had relevance in different factors of daily life, however, in many educational centers it has not been used for the benefit of education. The objective of this research was to influence the learning process of Geometric Solids through the use of a mobile application. The development of the application was proposed under the Mobile-D methodology and the name “ARmetry” was proposed. The experimental design of the quasi-experimental type was also chosen, where the population to be studied was 140 students and the sample was two sections of the morning shift, 70 students for the sample in total. Finally, it is concluded that using a mobile application with Augmented Reality positively influences the learning process in Geometric Solids.